Divergent evolution of male-determining loci on proto-Y chromosomes of the housefly - Li, Xuan; Visser, Sander; Son, Jae Hak; Geuverink, Elzemiek; Kıvanç, Ece Naz; Wu, Yanli; Schmeing, Stephan; Pippel, Martin; Anvar, Seyed Yahya; Schenkel, Martijn A; Marec, František; Robinson, Mark D; et al. (Nature communications, 2024)
Houseflies provide a good experimental model to study the initial evolutionary stages of a primary sex-determining locus because they possess different recently evolved proto-Y chromosomes that contain male-determining loci (M) with the same male-determining gene, Mdmd. We investigate M-loci genomically and cytogenetically revealing distinct molecular architectures among M-loci. M on chromosome V (MV) has two intact Mdmd copies in a palindrome. M on chromosome III (MIII) has tandem duplications containing 88 Mdmd copies (only one intact) and various repeats, including repeats that are XY-prevalent. M on chromosome II (MII) and the Y (MY) share MIII-like architecture, but with fewer repeats. MY additionally shares MV-specific sequence arrangements. Based on these data and karyograms using two probes, one derives from MIII and one Mdmd-specific, we infer evolutionary histories of polymorphic M-loci, which have arisen from unique translocations of Mdmd, embedded in larger DNA fragments, and diverged independently into regions of varying complexity.
Keywords: Houseflies; Y Chromosome; Sex Determination Processes; Genetic Loci; chromozom Y; Male; procesy určující pohlaví; molekulární evoluce; genetické lokusy; Animals; mužské pohlaví; chromozomy hmyzu; ženské pohlaví; Evolution, Molecular; Female; zvířata; moucha domácí; Chromosomes, Insect